A rare case of primary dermal clear cell sarcoma with focal epidermotropism: An entity difficult to distinguish from melanoma. (19th February 2020) - Nawrocki, Shiri; Fitzhugh, Valerie A.; Groisberg, Roman; Aviv, Hana A.; Maghari, Amin
Abstract: Clear cell sarcoma (CCS) is an uncommon soft‐tissue sarcoma that only rarely arises within the dermis. It is challenging to distinguish dermal CCS from nodular, primary dermal, or metastatic melanoma, as they share morphologic features and immunoprofiles. We describe a dermal CCS in a 25‐year‐old man with a cutaneous groin mass. The lesion was initially diagnosed as melanoma, likely metastatic. On consultation, in addition to a melanoma‐like tumor in the dermis, we identified focal infiltration of tumor cells into the overlying epidermis (epidermotropism), resembling primary nodular or metastatic melanoma. Given the patient's age and absence of a history of primary melanoma, fluorescence in situ hybridization (FISH) was performed, which revealed separation of the 5′ and 3′ EWSR1 probe signals on chromosome 22q12, prompting a diagnosis of CCS. Our case highlights the histopathological, immunohistochemical, and ultrastructural similarities between CCS and melanoma, and the consequent potential for major diagnostic confusion. In such cases, FISH analysis remains the key to diagnosis. CCS should be considered in patients with a melanoma‐like tumor in the dermis or subcutaneous tissue without epidermal (or with minimal) involvement, or prior to diagnosing metastatic melanoma in the absence of a known history of primary melanoma, especially in young individuals.